2013
DOI: 10.2500/aap.2013.34.3665
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biofilms and chronic rhinosinusitis

Abstract: Chronic rhinosinusitis (CRS) is a highly prevalent disease in the adult and pediatric population. It causes significant burden and the management is considered one of the most costly public health conditions. Comorbidities include asthma, aspirin sensitivity, and nasal polyposis. Staphylococcus aureus biofilms and exotoxins that act as superantigens have been implicated to play an important pathological role in the incidence, maintenance, and ongoing burden of CRS. A better understanding of the interplay betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…29 There are studies that looked at the role of S. aureus in the pathogenesis of CRS with inconclusive findings. 30,31 Although some of the studies within this review revealed an increase of S. aureus, it seems unlikely that S. aureus is the causative agent of the persistent inflammation in patients with CRS. However, the true role of this organism in CRS remains unclear.…”
Section: Discussionmentioning
confidence: 94%
“…29 There are studies that looked at the role of S. aureus in the pathogenesis of CRS with inconclusive findings. 30,31 Although some of the studies within this review revealed an increase of S. aureus, it seems unlikely that S. aureus is the causative agent of the persistent inflammation in patients with CRS. However, the true role of this organism in CRS remains unclear.…”
Section: Discussionmentioning
confidence: 94%
“…10 CRS is a highly prevalent disease in the adult and pediatric populations, and causes significant burden, and the management is considered one of the most costly public health conditions; comorbidities include asthma, aspirin sensitivity, and nasal polyposis. 11 Staphylococcus aureus biofilms and exotoxins that act as superantigens have been implicated as playing an important pathologic role in the incidence, maintenance, and ongoing burden of CRS. A better understanding of the interplay between bacterial factors, host factors, and the environment will facilitate better management of this disease.…”
Section: Epidemiologymentioning
confidence: 99%
“…Inflammation and biofilm infection have been implicated in the pathophysiology of CRS (Fokkens et al, 2012;Madeo and Frieri, 2013). Bacterial biofilms are a complex community of bacteria that form on both biotic and abiotic surfaces contained in a hydrated polymeric matrix (Costerton, Stewart, and Greenberg, 1999;Smith, Buchinsky, and Post, 2011).…”
Section: Discussionmentioning
confidence: 98%